JUNGLES OF RESISTANCE: READING ECOLOGICAL SUBJUGATION IN JOSEPH CONRAD’S HEART OF DARKNESS - Doni Efrizah; Purwarno Purwarno (University of Kuningan, 2026)
This study presents a contemporary ecocritical reading of Joseph Conrad’s Heart of Darkness, reexamining the African jungle not as a passive backdrop but as an active ecological agent that resists imperial domination. Employing a qualitative interpretive approach grounded in ecocriticism, the study combines close textual reading with thematic coding to analyze how the Congo River, the African jungle, and colonial infrastructures function as narrative sites of ecological agency. Drawing on recent formulations of slow violence (Davies, 2022), world-ecology (Moore, 2022), and ecofeminism (Gaard, 2022; Sharma & Joshi, 2024), the analysis demonstrates that Conrad’s natural landscapes register the cumulative ecological harm of imperial extraction while simultaneously destabilizing colonial authority. The findings reveal that the Congo River operates as an ecological witness to historical and environmental violence, the jungle emerges as a resistant and self-regulating ecological force that undermines imperial rationality, and colonial outposts symbolize the moral and ecological unsustainability of extractivist ideology. By foregrounding nature’s agency, the study shows how Heart of Darkness anticipates contemporary ecological concerns by linking environmental degradation with ethical and political collapse under empire. Beyond its theoretical contribution, this research highlights the pedagogical relevance of ecocritical literary analysis in English-as-a-Foreign-Language (EFL) contexts in Indonesia. Integrating ecocritical frameworks into literature instruction encourages students to develop critical literacy, environmental awareness, and ethical reflection. Overall, the study repositions Heart of Darkness as a narrative of ecological resistance, demonstrating its continued relevance to contemporary debates on environmental justice, colonial legacies, and sustainability in the environmental humanities.